Biohydrocarbon production for jet fuel from palm oil derivative products. Issue 1 (April 2020) - Neonufa, G F; Pratiwi, M; Puspawiningtiyas, E; Purwadi, R; Elizabeth, L
Abstract: Jet biofuel can be produced from vegetable oils and fats that are rich in lauric acid and myristic acid. Palm kernel oil is known to contain 47.8% lauric acid and 16.3% myristic acid. Jet biofuel production by the thermochemical method through decarboxylation of basic soap made from palm kernel oil has been extensively investigated. The objective of this study was to produce jet biofuel from basic soap made from palm kernel oil. Several metal compounds from the acetate group were selected for use in making basic soap. Decarboxylation of soap was carried out at 350°C and atmospheric pressure for 5 hours in the semi-batch reactor. Zinc metal enhances the yield of jet biofuel after decarboxylation of soap. Approximately 40 and 62 weight% of the jets biofuel had been obtained in this experiment.